THE ROLE OF SERVICE LEARNING IN PRE–SERVICE TEACHERS IN ENGLISH EDUCATION DEPARTMENT - kamal yusuf; Renaldi Bimantoro (SALEE: Study of Applied Linguistics and English Education, 2020)
Nowadays, pre-service teachers must collect teaching experiences as many as possible. The experiences will improve their self-confidence when they teach in the class. Self-confidence can make the students feel enjoy and comfort in the classroom. To get a lot of experience before to be a teacher, pre-service teachers can be volunteers to do service learning. Service learning can implement the pre-service knowledge when they got some supporting courses to help their when they teach in the class. The pre-service teachers do the service learning to be preparation for the future time because they will face in the real community. Basically, a good teacher must have high self-confidence, mastering in the material, and can make the students feel enjoy. In addition, the service learning can be as the reflection for the pre-service teacher. In fact, the service learning has so many benefit impacts for the pre-service teacher, the school, teacher, and the students. Keywords: Service Learning, pre-service teacher, teaching skill, English Teaching.